Ruling Second-hand Clothes Trade: An Analysis of International Environmental Law - Amalia Zuhra; Arlina Permanasari; Gisca Nurannisa; Idris, Siti Hafsyah; Nasywaan, Muhammad Falih (Lentera Hukum, 2025)
The second-hand clothing trade has emerged as a significant global industry, with the export and import of used clothing playing a vital role in the worldwide economy. However, the environmental impact of this trade has become a significant concern, particularly in developing countries that receive large quantities of used clothing. Reusing used clothing can be motivated by various considerations, such as charity, economic issues, reducing emissions and water use, and as benefits for prisoners during wartime. However, it is still unclear how much it can improve the sustainability of the apparel sector. According to the U.S. Environmental Protection Agency's most recent estimates, Americans dumped more than 21 billion pounds of clothing and other textiles into landfills in 2015. This amount is a significant increase from 12.5 billion pounds in 2000 and 4.6 billion pounds in 1980. Yet the proliferation of the inexpensive, disposable clothing known as "fast fashion" is one of the many environmental issues the apparel sector faces, along with water pollution and greenhouse gas emissions. Through normative library research using secondary data, this article examines the current international regulatory frameworks on the second-hand clothing trade and its environmental impacts. The finding highlights the importance of engaging stakeholders, including governments, NGOs, and the private sector, in developing more effective regulations and practices to regulate the environmental impact of the second-hand clothing trade. This article recommends more significant attention to the environmental effects of the second-hand clothing trade and for international regulations to be developed to promote more sustainable and responsible practices in this industry.Keywords: International Law, Enviromental Law, Thrifting Policy.